BECOMING CHINESE-AMERICAN: MINGLING IDENTITIES IN AMERICAN BORN CHINESE GRAPHIC NOVEL - Rasiah Rasiah; Nur Iklima Dewi (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2025)
This paper proposes to analyze the process of mingling of Chinese identity in the American-born Chinese graphic novel, published in 2006, written by Gene Luen Yang. The novel tells the story of Chinese immigrants from diverse social and ethnic backgrounds in the United States. They have to mingle their identity by mimicking the American culture to survive in the US society. In Bhabha's postcolonial theory, the mingling process is related to mimicry to negotiate identities. The Chinese immigrants tried to mimic the American culture and sustain their Chinese identity on the other side. From these two things, mimicry can be formed because of the process of ambivalence; these concepts are one of the formations of mimicry of culture. It is proposed not only to resist the stereotypical images associated to Chinese identities in the US but also to reveal the product of hybridity as a zone of resistance and creativity.